Keselamatan, Kesehatan Kerja Dan Lingkungan Hidup (K3lh) Pada Proyek Supermarket Jl. Sisingamangaraja XII KM. 3,3 - Lumban Gaol, Partahi; Saragih, Tiurma; Hasibuan, Peri Shandy (Jurnal Visi Eksakta, 2022)
Occupational safety, health and environment are all activities to ensure and protect the safety and health of workers through efforts to prevent work accidents and occupational disease in construction work. The purpose of this study is to determine the completeness of supporting facilities for the implementation of Health, Safety and Environment (OHSE) in the supermarket construction project on Sisisngamangaraja XII Km 3,3 Road. And to find out the application of OHSE and the obstacles that occur in the application of OHSE. Based on the results of the analysis of the research that has been done by distributing questionnaires to 47 project workers, the resulth of the completeness of supporting facilities fot he implementation of OHSE got the first/highest rank on the questionnaire. With the results of the data analysis of the completeness of supporting facilities for the implementation of OHSE, the mean is 4.4 with a standard deviation of 0.7. The implementation of OHSE in the project is going quite well and the obstacles that occur in implementating OHSE are among the workers namely the lack of awarness of workers about their own safety.